2013
DOI: 10.3389/fimmu.2013.00082
|View full text |Cite
|
Sign up to set email alerts
|

Costimulatory Molecules on Immunogenic Versus Tolerogenic Human Dendritic Cells

Abstract: Dendritic cells (DC) are sentinels of immunity, essential for homeostasis of T cell-dependent immune responses. Both functions of DC, initiation of antigen-specific T cell immunity and maintenance of tissue-specific tolerance originate from distinct stages of differentiation, immunogenic versus tolerogenic. Dependent on local micro milieu and inflammatory stimuli, tissue resident immature DC with functional plasticity differentiate into tolerogenic or immunogenic DC with stable phenotypes. They efficiently lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
163
2
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 202 publications
(187 citation statements)
references
References 139 publications
6
163
2
8
Order By: Relevance
“…Expression of surface molecules associated with DC maturation like CD83, the lymph node homing receptor CCR7 and MHC class-II molecules is reduced on IL-10-induced regDCs. In contrast, expression of inhibitory receptors such as immunoregulatory receptors like ILT2, ILT3, and ILT4 are increased on IL-10-induced regDCs, which has been suggested to be involved in tolerance induction [53]. The amount of proinflammatory cytokines released by IL-10-induced regDCs, like IL-6 and TNF-α, is similar to classically matured DCs.…”
Section: Immunosuppressive and Tolerogenic Activity Of Regulatory Denmentioning
confidence: 81%
See 3 more Smart Citations
“…Expression of surface molecules associated with DC maturation like CD83, the lymph node homing receptor CCR7 and MHC class-II molecules is reduced on IL-10-induced regDCs. In contrast, expression of inhibitory receptors such as immunoregulatory receptors like ILT2, ILT3, and ILT4 are increased on IL-10-induced regDCs, which has been suggested to be involved in tolerance induction [53]. The amount of proinflammatory cytokines released by IL-10-induced regDCs, like IL-6 and TNF-α, is similar to classically matured DCs.…”
Section: Immunosuppressive and Tolerogenic Activity Of Regulatory Denmentioning
confidence: 81%
“…In contrast, IL-10 production is dramatically increased suggesting another possible mechanism resulting in tolerance induction [54][55][56]. Several studies showed that in vitro generated tolerogenic IL-10-DCs have an even higher capacity to induce iTreg than tissue resident immature DCs [53]. Thus, a reduced expression of immunostimulatory molecules combined with a higher expression of inhibitory costimulators and the production of IL-10 may facilitate tolerogenic functions of IL-10-induced regDCs.…”
Section: Immunosuppressive and Tolerogenic Activity Of Regulatory Denmentioning
confidence: 96%
See 2 more Smart Citations
“…The fate of T cells is determined by the strength and kinetics of different costimulatory and co‐inhibitory molecules. Most studied co‐inhibitory molecules include CTLA‐4, programmed cell death protein 1 (PD‐1), and B‐ and T‐lymphocyte attenuator (BTLA) 40, 41…”
Section: Immune System and Its Complexitymentioning
confidence: 99%